ECO-INNOVATIVE SOLUTIONS FOR THE PROCESSING OF TECHNOGENIC MINERAL RESOURCES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
The inorganic wastes and residues formed during the production and operation process are valuable technogenic minerals, the rational treatment of which can reduce the amount of non-renewable natural mineral resources. The relatively low reuse of technogenic mineral resources is currently associated with specific characteristics of these resources. They have a wide and multiplex diversity in composition and structure, and hence a wide, uneven range of physical and chemical properties that require a complex approach to assessing the potential for developing each resource. In addition, it is necessary to evaluate the ecological and energy efficiency, technical feasibility and economic efficiency of the processing of these resources in comparison with the production of natural mineral substances from traditional technologies. A methodology for the evaluation production of potentially new goods from technogenic mineral waste is proposed. Parameters such as multifunctionality of new products, energy and resource saving, lifetime increase, reduction of negative impact on the environment, maintenance or improvement of production quality compared to original quality are taken into account. The basis for the analysis of these possibilities and methodology of assessment of eco-energetic efficiency to justify the usefulness of mineral wastes processing are given. Possibilities of using this approach for the development of mineral waste from construction and demolition recycling technologies for the production of composites, binders, fillers and monolithic structures are shown.